The Marriage Agreement in Article 29 of Law Number 1 of 1974 is Reviewed According to Islamic Law - Reka Desrina Wati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The purpose of this research is to determine the view of Islamic law on the Marriage Agreement in Article 29 of Law no. 1 of 1974. This research is juridical normative because it examines sources of written legal data and library materials by referring to the statute approach and syar'i approach related to Islamic law. The Sources of legal materials used in this study are primary and secondary legal materials. Marriage requirements can only be made before and at the time of the contract, where the contents must not conflict with the syari'at and the purpose of marriage. Ulama clarified that there is a marriage agreement that is shahih, which is that it has benefits and is in accordance with the purpose of the marriage, so this must be fulfilled, the conditions that fasid do not have to be fulfilled because there are parties who are hurt and it is against the law The contents of the agreement can include assets in marriage and other agreements. The agreement that has been made cannot be revoked again, because this is likened to a person who withdraws a gift that he has given and Rasulullah Saw strongly denounces this act. However, this is allowed if there is an agreement between both parties and neither party is disadvantaged.